Analisis Perhitungan Dan Pelaporan Pajak Pertambahan Nilai Dan Pajak Penghasilan Final Pada Pt. Griya Indah Persada (Fakultas Ekonomi Universitas Gresik, 2023)
Taxes have an important role in the source of state revenue in Indonesia. According to Director General of Taxes Suryo Utomo, tax revenue in Indonesia until the end of August 2022 will reach Rp. 1,171.8 trillion or grew by 58.1%. One type of tax that has experienced an increase is Value Added Tax and Final Income Tax. Value Added Tax is a tax imposed on delivery in the form of Taxable Goods or Services made within the customs area. Meanwhile, Final Income Tax is income tax that cannot be credited or deducted from the total amount of income tax payable at the end of the tax year. The purpose of this study is to find out how the calculation and reporting of Value Added Tax and Final Income Tax is carried out by a private company engaged in the Property and Real Estate sector and to find out the causes of underpayment or overpayment in Value Added Tax and the accuracy or delay of reporting the taxation. The results of the study show that the imposition of tariffs used as the basis for calculating the taxation is in accordance with the applicable Tax Law. While the reporting carried out by the company is fairly good because it never exceeds the due date of payment and reporting. The case of overpayment in VAT was caused by the company's success in utilizing the 0% DTP VAT program which was organized by the government from March to December 2021 and the number of input tax invoices received during certain tax periods but not accompanied by output tax invoices.